STRATEGI PEMASARAN UMKM DALAM PEMANFAATAN DIGITAL MARKETING UMKM DALAM BIDANG PERABOT RUMAH TANGGA DI DESA KAMPUNG BARU KABUPATEN TANAH BUMBU - MARYA YULLY C; Nadi Hernadi Moorcy (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2023)
The digital marketing trend is a business opportunity for MSMEs in the digital information era, one of which is in the form of digital marketing. Research purposes to find out how the digital marketing strategy by business actors must be applied by owners of micro, small and medium enterprises (MSMEs). And the impact of using digital marketing on increasing sales of micro, small and medium enterprise (MSMEs) products.Â Benefits of Research from Academic Aspects as a contribution of thought to other researchers in raising the same theme even though the time and object are different. Aspects of Knowledge Development As an application, especially marketing management in increasing knowledge and skills, especially regarding MSME Marketing Strategies in Utilizing MSME Digital Marketing in the Sector of Household Furniture.Â This research can add to and develop readers' insights regarding issues regarding MSME Marketing strategies in the Utilization of MSME Digital Marketing in the Field of Household Furniture.